Men with high dark triad personality traits can accurately infer dark triad traits from other people’s faces - Masui, Keita; Yoshizumi, Ryusei; Nakajima, Hina (Frontiers in Psychology, 2024)
Introduction The literature suggests that people can accurately infer dark triad (DT) personality traits from other peoples’ faces. Using a self-report scale, this study investigated the impact of participants’ DT personality traits on their ability to accurately infer other peoples’ DT traits from facial cues. Methods We created composite facial photographs of Japanese people with varying Machiavellianism, psychopathy, and narcissism scores. The Japanese participants (N = 170) assessed these three DT traits in the facial photographs and completed a questionnaire that assessed their own DT traits. Results The results indicated that the participants could accurately infer all three DT traits from female faces but not from male faces. Male participants showed a positive correlation between accurate inferences of other men’s Machiavellianism and their own DT traits. In contrast, female participants showed a negative correlation between correct inferences of men’s DT traits and their own DT traits. Discussion These findings offer novel insights into human evolutionary and social adaptations.